An Analytical Study of Morale and Efficiency among School Teachers in Gwalior City: Examining the Impact of Morale on Efficiency among School Teachers in Gwalior City (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study was an effort to find out the effect of Morale on efficiency. The research was done on 150 teachers of various private and government schools of Gwalior and Standardized Questionnaires based on a likert scale were used for the study. In this study regression analysis was applied in order to evaluate the influence of Morale on efficiency.Finally the study revealed that there is a significant and positive effect of Moraleon efficiency in School teachers of Gwalior region.